Local Breast Microbiota - Vitorino, Marina (2022)
Funding Information: D.A.C. has received honoraria from the Portuguese Navy, CUF Oncologia, and NTT DATA, and has served as a speaker, advisory board member, or has received research or education funding from AstraZeneca, CUF Oncologia, Daiichi Sankyo, Gilead, Hoffmann-La Roche, Merck KGaA, Merck Sharp & Dohme, Nestlé, Novartis, Pfizer, Nanobiotix, Puma Biotechnology Inc., Sanofi, Seagen Inc., and Uriage. Publisher Copyright: © 2022 by the authors.